2022
DOI: 10.3390/cells11132047
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Different TiO2-Based Phosphopeptide Enrichment and Fractionation Methods for Phosphoproteomics

Abstract: Protein phosphorylation is an essential post-translational modification that regulates multiple cellular processes. Due to their low stoichiometry and ionization efficiency, it is critical to efficiently enrich phosphopeptides for phosphoproteomics. Several phosphopeptide enrichment methods have been reported; however, few studies have comprehensively compared different TiO2-based phosphopeptide enrichment methods using complex proteomic samples. Here, we compared four TiO2-based phosphopeptide enrichment meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The purified samples were digested into peptides as previously described (53). Briefly, samples were reduced with DTT at a final concentration of 10 mM at 30 °C for 1 hour.…”
Section: In-solution Digestion Of Samplesmentioning
confidence: 99%
“…The purified samples were digested into peptides as previously described (53). Briefly, samples were reduced with DTT at a final concentration of 10 mM at 30 °C for 1 hour.…”
Section: In-solution Digestion Of Samplesmentioning
confidence: 99%
“…[33] ITO-coated material like other metal oxides utilized in metal oxide affinity chromatography (MOAC) has also been reported to possess a similar characteristic to electrostatically interact with polar species. [31,34,35] Compared to other purification methods, ITO material can be subjected to a wider pH range, which creates more possibilities for versatile sample handling processes and different pH-buffer treatments. [35] In previous studies, phosphopeptides were comprehensively investigated and proven to be retained by ITO-coated glass slide via the acid-base rinsing procedure and the phosphorylation sites were able to be deciphered with this approach.…”
Section: Introductionmentioning
confidence: 99%
“…[31,34,35] Compared to other purification methods, ITO material can be subjected to a wider pH range, which creates more possibilities for versatile sample handling processes and different pH-buffer treatments. [35] In previous studies, phosphopeptides were comprehensively investigated and proven to be retained by ITO-coated glass slide via the acid-base rinsing procedure and the phosphorylation sites were able to be deciphered with this approach. [35] It has been reported that the ITO-SPE method offers a faster manner to assist processing the samples, which we can save time preparing columns, loading samples, washing, and eluting the extracts with high pH solvents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations